Drinking water hygiene practices in caregivers of under 6 year children: a cross sectional study in urban Lucknow, India - Manar, Manish Kumar; Singh, Shivendra Kumar; Bajpai, Prashant Kumar; Singh, Shikhar (International Journal Of Community Medicine And Public Health, 2018)
Background: Safe drinking water is the basic necessity for humans. Due to water borne diseases, most of the children get malnourished. The present study was conducted to know about knowledge and practices on drinking water hygiene and to find the association between knowledge and drinking water hygiene practices among caregivers of under 6 year children. Methods: It is a community-based cross-sectional study conducted in the field practice area of a medical college in urban Lucknow. We included 250 respondents in our study. The data were analyzed using Institutional SPSS-24.0 (IBM Corp., Chicago, USA). Results: The present study showed that about 91.6 percent of study participants showed concern about safe drinking water hygiene. About 90.8 percent of study participants thought that water container needs cleaning and about 95.6 percent thought that water container needs covering. Surprisingly 65.6 percent of the participants did not use any type of water purification method. People thought that they should use drinking water purification methods, but in reality, much less percentage (34.4%) of people in the study uses any type of purification method (p<0.001). Conclusions: Although most of the participants showed their concern about safe drinking water hygiene, purification, etc., most of them still do not use any purification methods putting their children are at risk of many diseases.